Molecular characterization and bioremediation effectiveness of Limnospira platensis cultivated in swine wastewater: biochemical analysis and assessment of the resulting biomass as a cucumber biostimulant - Álvarez-Montero, Xavier; Mercado-Reyes, Ingrid; Jaramillo-Salazar, Lady; Jácome-Gómez, Leonardo; Castillo-Chamba, Wilian; Ulloa-Mercado, Gabriela; Renteria-Mexía, Ana; Santos-Ordóñez, Efrén (Frontiers in Environmental Science, 2026)
The escalating global demand for water resources, combined with anthropogenic pollution, poses a significant threat to the availability of potable water. Even small-scale pig farms generate enough wastewater to pose environmental risks. Microalgal wastewater treatment offers an effective solution for pollutant recycling, providing advantages such as reduced energy consumption, lower greenhouse gas emissions, and greater cost efficiency compared to conventional methods. The biomass produced through this process has multiple valuable applications, including use as a biostimulant and biofertilizer. Consequently, this study investigates the use of the microalga Limnospira platensis for the biological treatment of undiluted pig slurry, intending to develop a sustainable biostimulant. Initially, a molecular characterization of the Limnospira platensis strain was performed to verify its identity. The research employed 150 mL bubble column photobioreactors (BCPs) with a continuous airflow of 15 mL min-1, followed by the application of the resulting biomass as a biostimulant for Cucumis sativus. The productivity of Limnospira platensis was monitored daily in cultures grown in pig slurry. The results demonstrated that Limnospira platensis effectively treated pig slurry, producing biomass at a concentration of 1.34 g L-1, and a productivity of 0.88 g L-1 day-1. The highest removal efficiencies recorded were 99.93% for Chemical Oxygen Demand (COD), 94.83% for total phosphorus (TP), 98.93% for total nitrogen (TN), and 100% for NH4+ and total coliforms. The most favorable biostimulant effect of Limnospira platensis biomass on C. sativus was observed in T2 (0.5 g L-1 with centrifugation and cellular disruption), which yielded a germination index of 515.34% ± 81.81%, a shoot number of 2.20 ± 0.04, and a root number of 10.33 ± 0.17. These findings demonstrate the feasibility of using microalgae to treat wastewater with high organic loads, highlighting the significant biostimulatory potential of the biomass produced in these treatment systems.